Smoking asthmatics - Thomson, Neil (Henry Stewart Talks, 2011)
High prevalence rates of smoking in asthma, Detrimental effects of smoking on clinical outcomes, Impaired response to corticosteroids, Mechanisms of adverse effects, Management includes smoking cessation, but optimum drug therapy not established